2009
DOI: 10.1029/2008ja013749
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Point Equatorial Experiment (COPEX) campaign in Brazil: Electrodynamics highlights on spread F development conditions and day‐to‐day variability

Abstract: [1] A Conjugate Point Equatorial Experiment (COPEX) campaign was conducted during the October-December 2002 period in Brazil, with the objective to investigate the equatorial spread F/plasma bubble irregularity (ESF) development conditions in terms of the electrodynamical state of the ionosphere along the magnetic flux tubes in which they occur. A network of instruments, including Digisondes, optical imagers, and GPS receivers, was deployed at magnetic conjugate and dip equatorial locations in a geometry that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 88 publications
8
142
0
Order By: Relevance
“…The role of the PRVD on the onset of RTI leading to the formation of EPB structures and, consequently, to the presence of the irregularities producing scintillation is already known either in the form of preconditioning (e.g., Abdu, 2001;Abdu et al, 2009) or in the form of seeder (Woodman, 1994;Sousasantos et al, 2013). The PRVD is responsible for altering some critical parameters of the equatorial ionospheric plasma, such as the collision frequency between ions and neutrals and the density gradient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the PRVD on the onset of RTI leading to the formation of EPB structures and, consequently, to the presence of the irregularities producing scintillation is already known either in the form of preconditioning (e.g., Abdu, 2001;Abdu et al, 2009) or in the form of seeder (Woodman, 1994;Sousasantos et al, 2013). The PRVD is responsible for altering some critical parameters of the equatorial ionospheric plasma, such as the collision frequency between ions and neutrals and the density gradient.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the PRVD in the development of irregularities has been widely discussed and the necessity of its existence as a requirement for subsequent EPB development is already well established. Abdu et al (2009), using measurements from a network of instruments during COPEX campaign (Conjugate Point Equatorial Experiment), argued that in the Brazilian longitudinal sector a threshold value around 22 m s −1 of prereversal vertical drift peak (V pk ) is needed for the development of the EPB structures. However, slightly smaller values of V pk may provide an ambient where spread F at the bottom side may occur, although it does not evolve into EPB structures.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [2010a] presented the profile of the ion vertical drift with height measured by the Jicamarca incoherent scatter radar in a case and found that the variation of the ion drift was small over the altitude range of 200-700 km. On the other hand, Abdu et al [2009] showed that altitude variation of the zonal electric field in the postsunset equatorial ionosphere indeed occurred. In the cases presented in Figures 1 and 3, the altitude of C/NOFS varied in the range of 400-460 km between 17:00 and 23:00 LT. We assume that Figure 4 represents the variation of the ion drift with local time, rather than with altitude, because the change of altitude was not large.…”
Section: Observationsmentioning
confidence: 97%
“…A possible cause for this feature is the vertical gradient in the zonal electric field (the vertical prereversal enhancement). Abdu et al [2009] found that the zonal electric field in the equatorial ionosphere could vary with altitude and that the altitude variation could depend on longitude. During Orbit 19016 of Figure 1, C/NOFS was located at 13.8 magnetic latitude at 19:00 LT, and the altitude of C/NOFS was 432 km.…”
Section: Observationsmentioning
confidence: 99%
“…The best fit line nearly demonstrates a 1-to-1 correspondence, with a slope of 1.09 and intercept of À0.06 mV/m. Previous studies have shown the existence of altitude gradients in the zonal electric field [Abdu et al, 2009;Pingree and Fejer, 1987], which could explain some of the scatter in the figure, since the JULIA measurements are taken at 150 km, while we use C/NOFS data between 400 and 500 km altitude. But in general, this result indicates the C/NOFS IVM measurements are a good proxy for E-region electric fields.…”
Section: Comparison With C/nofsmentioning
confidence: 99%